Implementasi Pembangunan Infrastruktur di Desa Cinta Rakyat Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Cindy Nababan; Bila May; Dandi Putra Bintang; Julia Ivanna (Journal on Education, 2024)
The development of housing infrastructure through individual participation and community participation in local communities becomes infrastructure that builds the economy of the Cinta Rakyat Village community. Currently, infrastructure development in Cinta Rakyat Village is experiencing good progress, driven by the local community's need for good infrastructure. This research is in accordance with qualitative methods with a descriptive approach. Qualitative research was chosen as the type of research used in this research. The choice of qualitative research is because there are several factors that take precedence in terms of elaborating and explaining a phenomenon to be studied. In qualitative research there is also more explaining, describing and more analysis using an inductive approach. The data collection techniques used by researchers are techniques from relevant sources. In this case, the focus of various in-depth reference sources is the presence of key informants who have previously been given access to provide in-depth questions related to the problem topic being researched. Infrastructure has an important role as one of the driving wheels of economic growth and the development of physical facilities and infrastructure or often referred to as infrastructure is a very important part of the public service system. Development of rural transportation infrastructure to support increased accessibility for rural communities.